2006
DOI: 10.1021/bm060365x
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory Polysaccharides from Chlorella pyrenoidosa. A New Galactofuranan. Measurement of Molecular Weight and Molecular Weight Dispersion by DOSY NMR

Abstract: Fractionation of the hot water extract of Chlorella pyrenoidosa was performed using a combination of ethanol precipitation, size exclusion chromatography, and anion exchange chromatography. One fraction contained a new polysaccharide, and this compound was shown to be a 1-->2-linked beta-d-galactofuranan from its 1D and 2D (1)H and (13)C NMR spectra, with a molecular weight of 15 kDa from DOSY NMR measurements. A number of other fractions were shown to have the same repeating unit as the previously identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Currently, Chlorella is produced by more than 70 companies (Spolaore et al 2006) and contains several novel properties. A special polysaccharide is considered as the most important substance and serves as active immunostimulator, free-radical scavenger and reducer of blood lipids (Suárez et al 2005;Suárez et al 2006). Other healthpromoting effects of Chlorella are the lowering of cholesterol (Fujiwara et al 1990), preventive action against artherosclerosis (Sano and Tanaka 1987) or antitumor action (Noda et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Chlorella is produced by more than 70 companies (Spolaore et al 2006) and contains several novel properties. A special polysaccharide is considered as the most important substance and serves as active immunostimulator, free-radical scavenger and reducer of blood lipids (Suárez et al 2005;Suárez et al 2006). Other healthpromoting effects of Chlorella are the lowering of cholesterol (Fujiwara et al 1990), preventive action against artherosclerosis (Sano and Tanaka 1987) or antitumor action (Noda et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…PV-P2 and PV-P3 also increased the production of NO, TNF-␣, and IL-6 in a dose-dependent manner, but were less effective than PV-P1. This may be attributed to the higher molecular weight and higher degree of branching of PV-P1 [12]. All three fractions had strong immunomodulatory activities.…”
Section: Immunomodulatory Activitiesmentioning
confidence: 92%
“…Previous reports have shown that the anti-cancer activity and immunomodulatory activity are related to the triple helical conformation of (1→3)-␤-glucan main chain for some polysaccharides, such as lentinan isolated from the fruit body of Lentinula edodes [11]. The arabinogalactans with higher molecular weight, extracted from Chlorella pyrenoidosa cells, showed immune-stimulatory activity, but low molecular weight fractions did not [12]. To date, some polysaccharides have been isolated from the fruit clusters of P. vulgaris using different methods [3,4].…”
Section: Introductionmentioning
confidence: 94%
“…The HOD signal was achieved by a presaturation for 0.5 s. NMR diffusion ordered spectroscopy (DOSY) experiments were carried out using the standard pulse sequence on the same AV-600 NB spectrometer for determination of molecular weight. The equation for DOSY experiments was as follows [17];…”
Section: Instruments In Structural Determination Of β-13-mentioning
confidence: 99%
“…Recently, investigators developed NMR DOSY as a useful tool for measurement of molecular weights, including those of polysaccharides [17,23]. Using the equation in the experimental section, the estimated molecular weight of LMG is 3979 Da.…”
Section: Molecular Weights Of Lmg As Determined Using Nmr and Maldi-tmentioning
confidence: 99%